Penerapan Strategi Pembelajaran Matematika Dengan Student Team Achievement Division Dan Numbered Head Together Terhadap Hasil Belajar Ditinjau Dari Kemampuan Awal Di SMP Negeri 1 Nguter Kabupaten Sukoharjo - Sumardi, Sumardi, Prof. Dr. Sutama,M.Pd, Prof. Achmad Fathoni,.M.Pd (2017)
This research is aimed to examine 1) to analyze and examine the influence of STAD and NHT learning strategic toward the learningresult, 2) to analyze and examine the influence of the beginning ability toward the learning result, 3) to analyze and examinethe interaction of learning strategic and the beginning ability toward the mathematic learning result. The research design is Experimental Quasi.The populationof this research was all the seventh year students of SMP N 1 Nguter Sukoharjo. The removal of the sample is bycluster sampling. The method of the data collecting is by documentation and test. The population of the research is all students of seven grade of SMP N 1 Nguter in 2015/2016 that consist of eigh classes. The analysis technic is two ways of different cell Anava, to be continued with Scheffe method. The result of the research by the significance level 0,05 shows 1) The students learning result with STAD strategic isbetter than NHT, 2) The students learning result of the high beginning ability is better than the students who have medium and low beginning ability, the students learning result of the medium beginning ability is better than the students who have low beginning ability, 3) STAD strategic is more effective than NHT to the students who have medium beginning ability. Concerning with STAD strategic, the learning result of the students who have high beginning ability is as same as the students who have medium beginning ability, and the learning result of the students who have high and medium beginning ability is better than the students who have low beginning ability. While on the NHT strategic, the learning result of the students who have high beginning ability are better than the students who have medium and low beginning ability. Whereas the students who have medium and low beginning ability got the same learning result.